Method for automatic compensation of a single-phase earth fault - Martebe K. Zhankuanyshev; Bibara Zh. Kushkimbayeva; Sofya Sh. Egemberdieva; Zhanar S. Esdauletova; Laura N. Yesmakhanova (Bulletin of Electrical Engineering and Informatics, 2021)
The paper demonstrates improving the reliability of power supply and operating safety of power receivers in electric networks of 6-10 kV, by controlling the neutral mode in extended electric networks of 6-10 kV with capacitive earth fault currents above 15 A. The purpose of the study is to increase the reliability of power supply and the safety of operation of power receivers in such electric networks, the establishment of patterns in controlling the neutral mode in extended 6-10 kV electric networks with capacitive earth fault currents above 15 A, as well as the development of a method and device automatic detection of single-phase earth fault current. Grounding methods and neutral modes in electric networks with a voltage of 6-10 kV are considered. The method and device for automatically determining the current of a single-phase earth fault were developed. In the result, the relationship between the active and inductive components of the neutral current during series RL grounding of the network Ia/IL=(0.5÷0.3) was established, which ensures reliable operation of the SPEF protection of both current and directional principles including the changes of capacity abruptly networks caused by switching outgoing lines.